2012
DOI: 10.1155/2012/798502
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Tuberculosis in Cattle in the Highlands of Cameroon: Seroprevalence Estimates and Rates of Tuberculin Skin Test Reactors at Modified Cut-Offs

Abstract: The aim of this study was to obtain epidemiological estimates of bovine tuberculosis (TB) prevalence in cattle in the highlands of Cameroon using two population-based tuberculin skin test (TST) surveys in the years 2009 and 2010. However, prior to the TST survey in 2010, blood was collected from already chosen cattle for serological assay. Anti-bovine TB antibodies was detected in 37.17% of tested animals and bovine TB prevalence estimates were 3.59%–7.48%, 8.92%–13.25%, 11.77%–17.26% and 13.14%–18.35%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 42 publications
3
15
1
Order By: Relevance
“…Bovine tuberculosis (bTB) is an important neglected zoonosis in Cameroon, where many communities depend on their livestock for livelihood and the incidence of human TB and TB-HIV/AIDS coinfection are high and increasing annually [8]. It is mainly caused by Mycobacterium bovis which can also cause disease in human and in a variety of domestic and wild animals [8].…”
Section: Mycobacterium Species Infecting Humans In Cameroonmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine tuberculosis (bTB) is an important neglected zoonosis in Cameroon, where many communities depend on their livestock for livelihood and the incidence of human TB and TB-HIV/AIDS coinfection are high and increasing annually [8]. It is mainly caused by Mycobacterium bovis which can also cause disease in human and in a variety of domestic and wild animals [8].…”
Section: Mycobacterium Species Infecting Humans In Cameroonmentioning
confidence: 99%
“…Bovine tuberculosis (bTB) is an important neglected zoonosis in Cameroon, where many communities depend on their livestock for livelihood and the incidence of human TB and TB-HIV/AIDS coinfection are high and increasing annually [8]. It is mainly caused by Mycobacterium bovis which can also cause disease in human and in a variety of domestic and wild animals [8]. A study done by Ndukum et al in littoral and West region of Cameroon showed that TB lesions are common pathologies identified in slaughtered cattle and rates ranging from 0.18% to 4.25% have been recorded [9,10].…”
Section: Mycobacterium Species Infecting Humans In Cameroonmentioning
confidence: 99%
“…For example previous studies in Cameroon have reported bTB prevalence between 0.1–4.3% using lesion detection in abattoir based studies [ 22 – 24 ]. Higher prevalences have been reported using ante-mortem diagnostics (3.5–18.4%) such as the single comparative intradermal skin test and even higher using a serological assay high (37.2%)[ 25 27 ]. Furthermore the awareness of bTB and the extent of milk consumption within Cameroonian cattle keeping communities is poorly understood with only previous studies limited to butcher’s knowledge of bTB [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…While rapid test kit alone may not be reliable for screening bovine TB and additional tests is required to validate its results [18]. However, tuberculin skin test and anti BTB antibody tests (lateral flow) when used in parallel presented an amended detection of BTB compared to the results of each test [19]. There are paucity in reports concerning prevalence of bovine tuberculosis in Iraq, especially in last three decades, this could attributed partly to the cost and unavailability of a reliable and less cumbersome diagnostic screening test and political will to diagnose and eradicate the disease in livestock need to be improved more importantly.…”
Section: Introductionmentioning
confidence: 99%